Efficacy of cetuximab-based chemotherapy in metastatic colorectal cancer according to RAS and BRAF mutation subgroups: A meta-analysis - LIN, LI (Mol Clin Oncol, 2016)
The epidermal growth factor receptor (EGFR)-targeting monoclonal antibody, cetuximab, has been added to standard chemotherapy regimens for treating metastatic colorectal cancer (mCRC). However, the efficacy of adding cetuximab to chemotherapy regimens for patients of differing genetic backgrounds remains controversial. The present study aimed to investigate the efficacy of adding cetuximab to chemotherapeutic regimens in subgroups of patients defined according to the RAS and BRAF mutation status in the first-line treatment of patients with mCRC. A systematic literature search was performed in databases (including PubMed, Embase, the Cochrane library, the American Society of Clinical Oncology and the European Society For Medical Oncology) up to August 2015. Randomized controlled trials analyzing overall survival (OS) and progression-free survival (PFS) in mCRC treated with cetuximab, and grouped by RAS and BRAF mutation status, were identified. The major outcome measures were hazard ratios (HRs). Pooled HRs were calculated using fixed- or random-effects models, according to the magnitude of the heterogeneity. A total of nine studies met the inclusion criteria. Use of cetuximab was significantly associated with longer OS in KRAS exon 2 wild-type tumors [HR=0.87, 95% confidence interval (CI)=0.79–0.96, Z=2.91, P=0.004] and wild-type KRAS/RAS (in exons 2, 3 and 4 of KRAS and exons 2, 3 and 4 of an associated gene, NRAS; HR=0.72, 95% CI=0.60–0.85, Z=3.74, P=0.0002). No significant differences in OS and PFS were identified between KRAS exon 2 mutations and tumors with the other RAS mutations (in exons 3 and 4 of KRAS and exons 2, 3 and 4 of an associated gene, NRAS). The meta-analysis demonstrated that cetuximab-based chemotherapeutic regimens led to a marked improvement in OS in patients with mCRC who lacked any RAS mutations (either KRAS exon 2 or any other RAS mutation). By contrast, the subgroup analyses revealed no evident PFS or OS benefit in using cetuximab for patients with any RAS mutation. Taken together, the evidence indicates that cetuximab should only be used for mCRC patients with the wild-type RAS gene. Some benefits were observed in patients with wild-type KRAS/BRAF who received cetuximab-based chemotherapy, even though there were insufficient data to perform meta-analysis with the BRAF mutation status.